Healthy food choice: Survey results from Iranian consumers toward antibiotic‐free chicken. Issue 1 (30th January 2017) - Rahnama, Hassan; Fadaei, Mehdi; Baghersalimi, Saeed
Abstract: Demand for healthy food is increasing in Iran. Although demand for these foods has increased, the real benefits and purchasing patterns are not known. The purpose of this study is to identify factors affecting consumer choice behavior toward antibiotic‐free chicken, and examines whether there are significant differences in importance of these factors between consumers with different outlooks. Logistic regression, chi‐square, and Friedman test were applied to assess collected data by a questionnaire survey. The results indicated that perception, awareness, motivation, social factors, and lifestyle had significant influence on the choice of antibiotic‐free chicken and demographic factors had no influence on it. Among effective factors, perception, and motivation have the most and least effect on choice of antibiotic‐free chicken, respectively. Practical applications: These results are relevant to sensory scientists and healthy foods producers, especially antibiotic‐free chicken producers are interested to know how different factors will be able to impact on consumers' choice behavior. There is less information in the literature about consumer choice behavior toward antibiotic‐free chicken in Iran and another country. A better understanding of consumer choice behavior can be beneficial to develop this kind of product, and help poultry industry activists to encourage consumer to buy healthy products. The study showed that consumers' perception including high quality, appropriate packaging, cleanness of store, and credible brand are the most influential factors on consumer choice behavior. The researchers' findings might suggest the importance of social factors and raise of awareness as another important factors through consumers approach.